Energy storage System the Hybrid Battery Charging by Used the Wireless Power Transfer for the Electric Vehicles - Tawatchai Jitson; Siriruch Cheapanich (My University, 2021)
This paper discusses the charging of an electric vehicle using wireless power transfer (WPT). Today electric vehicles around the world used long life time batteries and fast charging increases the travel range. The problem with the power supplied to electric vehicles are charged the battery takes a long time. But the ability of supercapacitors can be stored energy faster than batteries. The batteries are lower in energy than supercapacitors. In the study, both devices are used to charge wireless power transmission and power the motor drive. The performance of the battery and supercapacitor in the electric vehicles mileage test when an alternated power supply is added to the motor drive while the electric vehicles are in motion. This research provides information on how to develop energy storage systems for future work.
Keywords: Wireless Power Transfer Systems; Advanced Battery Technologies Research; Energy Harvesting in Wireless Networks